2021
DOI: 10.1088/1741-4326/ac21f9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated ELM and divertor power flux control using RMPs with low input torque in EAST in support of the ITER research plan

Abstract: suppression in ITER high Q DT scenarios since they provide optimum integration features regarding energy and particle confinement, pellet fuelling, radiative divertor operation while eliminating ELM transient power loads and being compatible with low torque input.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
(67 reference statements)
3
17
0
Order By: Relevance
“…In principle, therefore, our two-fluid CUTIE model predicts both the transition, the near-complete mitigation of the type-I ELMs and the existence of a ‘point/discrete spectrum (coherent modes)’ after transitions, which may manifest as observable oscillations near 0.9 , near the plasma edge. These findings bear a close qualitative resemblance to recent experimental observations [ 21 ] and may have important implications for RMP suppression of ELMs on ITER [ 27 ]. We next turn to the question of how the transitions in the turbulence (both waveform amplitudes and spectral characteristics) affect the global properties such as ‘Density pump out’ and ) post-transition.…”
Section: Results Of Simulationssupporting
confidence: 86%
“…In principle, therefore, our two-fluid CUTIE model predicts both the transition, the near-complete mitigation of the type-I ELMs and the existence of a ‘point/discrete spectrum (coherent modes)’ after transitions, which may manifest as observable oscillations near 0.9 , near the plasma edge. These findings bear a close qualitative resemblance to recent experimental observations [ 21 ] and may have important implications for RMP suppression of ELMs on ITER [ 27 ]. We next turn to the question of how the transitions in the turbulence (both waveform amplitudes and spectral characteristics) affect the global properties such as ‘Density pump out’ and ) post-transition.…”
Section: Results Of Simulationssupporting
confidence: 86%
“…While maintaining the desired ELM phase, the control of steady-state divertor heat loads by divertor detachment is simultaneously required in high-performance future tokamaks, including ITER. To achieve this operational regime, experimental and theoretical studies on the compatibility of RMPinduced ELM control with detachment have been conducted [16,17]. Also, impurity-seeded detachment, as well as ELM suppression, was experimentally achieved [18].…”
Section: Introductionmentioning
confidence: 99%
“…At these levels, MHD currents in the plasma may be strong enough to modify the vacuum magnetic field, thus resulting in the magnetic topology changes [8][9][10][11][12]. Previous studies have also showed that the divertor plasma operation is highly dependent on the magnetic topology [13][14][15][16][17][18][19][20][21][22][23][24]. Therefore, the study on edge plasma transport with finite beta effects is an essential topic for high-performance plasmas in future W7-X experiments.…”
Section: Introductionmentioning
confidence: 99%